Evidence of New Immigrant Assimilation in Canada: An Update - Yu, Xiaoye (Université d'Ottawa | University of Ottawa, 2009)
This paper uses the public use 1991, 1996 and 2001 Canadian census microdata files to analyze the earnings performance of immigrants relative to the Canadian-born. My results show that recent immigrant cohorts fared better in the period of 1995-2000 relat